YouTube's Impact on Gadget Buying Behaviors of Generation Z - Ganesan , D.; Jaiganesh , G. (An Overview on Business, Management and Economics Research Vol. 5, 2023)
This chapter explores about YouTube's impact on Generation Z's buying behavior, surveying 200 participants to examine demographics, viewing habits, and trust in YouTuber reviews. Results highlight YouTube's pivotal role; 51% base purchases on reviews, 82.5% find them crucial, and 60% strongly trust YouTubers. Positive comments significantly impact interest, scoring 64.80. Factors influencing consumers include product usefulness (62.73%) and influencer credibility. These findings stress ethical influencer collaborations and cost-effective marketing. As social media evolves, YouTube remains vital for brands connecting with Generation Z.